Creating an augmented possession framework to evaluate phases of play and application in international football - Deb, B.; Fernandez-Navarro, J.; Jarman, I.; McRobert, A. P. (Journal of Sports Analytics, 2025)
Performance analysts routinely perform game plan evaluations of their in possession play, breaking it down into phases: 1st Phase, 2nd Phase, Final Phase and Transition Defence to Attack. To evaluate a team's performance in relation to their game plan, this study showcases a framework to allow the measurement of tactical strategies in different phases of the game. This framework augments possession sequence data, a series of on-ball events until a stoppage or turnover, with notational analysis data (phases of play and phase outcomes) to evaluate team style and performance across 82 international football matches from 2018 to 2022. From this enhanced possession framework, we assessed the impact of specific events, i.e., progressive passes on phase outcomes, by conducting a series of mixed effects multivariable logistic regression models. Progressive passing showed increased odds of positive phase outcomes when attempting to enter the Final Phase including successful phase progressions (aOR 2.57 [2.19-3.02]), dangerous possession (aOR 1.79 [1.56-2.04]), shot (aOR 1.70 [1.44-2.01]), critical chance (aOR 1.91 [1.27-2.86]), and goal (aOR 2.05 [1.34-3.12]). This framework has allowed the development of novel metrics and visualisations, such as how teams create dangerous possessions, which aids the post-match review process.